Critical level of phosphorus in cotton plants I: plant growth as a function of available phosphorus - Medeiros, A.A.de; Haag, H.P. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1990)
In order to establish the critical level of phosphorus in annual varieties of IAC-17, LAC-19, IAC-20, CNPA 78/SME-4 and in perennial varieties CNPA 2M and CNPA 3M, young cotton plants were grown in nutrient solutions containing the following phosphorus concentrations: 0.38ppm, 1.14ppm, 3.42ppm, 10.26ppm and 30.78ppm. Plants were harvested when 75 days old. Plant height and dry weight of roots, stem and leaves were determined. The authors concluded that available P for all varieties is in the range between 19.20 and 21.9ppm.